PENGARUH PRAKTIK KERJA INDUSTRI TERHADAP KESIAPAN KERJA SISWA KELAS XI SMKN 2 PEKANBARU - Andri, Doni; Syahza, Almasdi; ', Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to identify and measure the impact of work readiness against Prakerin the student SMKN 2 Pekanbaru. Prakerin (Industrial work practices) or often reffered to the practice of field work (PKL) is part of the education of dual sistem as the program of cooperation between vocational High School and companies in the industry.Regarding to Prakerin, students are experted to gain work in the world of business and industry. Data source of this study retrieved from the questionaireswhich has been filled in by the student of SMKN 2 as the sample that meet the criteia. The result showed that the Prakerin has effect on student work readiness.it is because students that gain Prakerin experience have better work readiness compared to the student that have Lack Prakerin experienceKeywords: Industrial Work Praktices, Work Readines, Vocational Hight School Student